Hubungan Tingkat Kegawatdaruratan Pasien dengan Tingkan Kecemasan Keluarga Pasien di IGD RSI Sultan Agung Semarang - Norfita Ashari; Erna Melastuti; Ahmad Ikhlasul Amal (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Patients who come to the emergency room will be triaged. Categorization of patients based on triage often causes anxiety in the patient's family. Anxiety is a psychological condition of a person with fear accompanied by physical complaints. The purpose of this study was to determine the relationship between the level of patient emergency with the level of anxiety of the patient's family in the emergency room of RSI sultan agung Semarang. This study is a type of quantitative research with correlational research design and cross sectional method. Data collection was done with a questionnaire with a total of 300 respondents with accidental sampling technique. The data obtained is statistically processed using the sommers test. Based on the analysis obtained, 41 respondents in ATS 2 experienced very severe anxiety, 63 respondents in ATS 3 experienced severe anxiety, 47 respondents in ATS 4 experienced moderate anxiety, 10 respondents in ATS 5 experienced mild anxiety. The results of the sommers test showed a p value of 0.00, meaning that there was a relationship between the level of emergency of the patient and the level of anxiety of the patient's family in the emergency room of RSI sultan agung Semarang.